Clinical utility of target amplicon sequencing test for rapid diagnosis of drug-resistant Mycobacterium tuberculosis from respiratory specimens - Leung, Kenneth Siu-Sing; Tam, Kingsley King-Gee; Ng, Timothy Ting-Leung; Lao, Hiu-Yin; Shek, Raymond Chiu-Man; Ma, Oliver Chiu Kit; Yu, Shi-Hui; Chen, Jing-Xian; Han, Qi; Siu, Gilman Kit-Hang; Yam, Wing-Cheong (Frontiers in Microbiology, 2022)
An in-house-developed target amplicon sequencing by next-generation sequencing technology (TB-NGS) enables simultaneous detection of resistance-related mutations in Mycobacterium tuberculosis (MTB) against 8 anti-tuberculosis drug classes. In this multi-centre study, we investigated the clinical utility of incorporating TB-NGS for rapid drug-resistant MTB diagnosis in high endemic regions among southeast China. From January 2018 to November 2019, 4,047 respiratory specimens were available from patients suffering lower respiratory tract infections in Hong Kong and Guangzhou, among which 501 were TB-positive as detected by in-house IS6110-qPCR assay with diagnostic sensitivity and specificity of 97.9% and 99.2% respectively. Preliminary resistance screening by GenoType MTBDRplus and MTBDRsl identified 25 drug resistant specimens including 10 multidrug-resistant TB. TB-NGS was performed using MiSeq on all drug-resistant specimens alongside with 67 pan-susceptible specimens, and demonstrated 100% concordance to phenotypic drug susceptibility test. All phenotypically resistant specimens with dominating resistance-related mutations exhibited a mutation frequency of over 60%. Three quasispecies were identified with mutation frequency of less than 35% among phenotypically susceptible specimens. They were well-distinguished from phenotypically resistant cases and thus would not complicate TB-NGS results interpretations. This is the firsta large scale pstudy that explored the use of laboratory-developed NGS platforms for rapid TB diagnosis. By incorporating TB-NGS with our proposed diagnostic algorithm, the workflow would provide user-friendly, cost-effective routine diagnostic solution for complicated TB cases with an average turnaround time of 6 working days. This is critical for timely management of drug resistant TB patients and expedite public health control on the emergence of drug resistant TB